Survei Pembinaan Prestasi Olahraga Sepaktakraw Pada Atlet Pemusatan Pendidikan dan Latihan Olahraga Pelajar Daerah (PPLPD) Kabupaten Kendal 2022 (Indonesian Journal for Physical Education and Sport, 2022)
The focus of this research is to find out the conditions and problems of developing the performance of the Kendal PPLOPD Sepaktakraw team regarding the organization, athletes, coaches, implementation of training programs, facilities and infrastructure, and achievements that have been obtained. Researchers used descriptive qualitative research methods that used three research instruments in the form of interview guidelines, observation guidelines, and documentation. The results of the research that have been carried out can be concluded that the program and athlete coaching at PPLOPD Kendal district has gone through good stages, but there are few suggestions that must be submitted by researchers. The facilities and infrastructure needed for athletes are more considered in the process of procurement and improvement of existing facilities. So that athletes are more enthusiastic in practicing so that their performance will be more promising